Bid Collusion in Public Procurement Law - Skrobotowicz, Martyna (Zmowa przetargowa w Prawie zamówień publicznych, 2023)
Unlawful agreements restricting competition, also known as bid rigging, is one of the acts of unfair competition specified by antitrust law. Its occurrence is associated with many unwelcome market practices, which is why it is considered to be a highly undesirable phenomenon and eliminated from economic turnover. In the field of public procurement, the phenomenon of bid rigging is particularly harmful because it leads to the inefficient management of public funds. For this reason, the legislator has included rules that prevent bid collusion in public procurement law institutions, assisting the contracting authority in protecting the competitiveness of the procedure. This paper focuses on a comparative analysis of the model of bid collusion, regulated under the Act on Competition and Consumer Protection with the provisions of Public Procurement Law. The act distinguishes bid collusion as a prerequisite for the subjective exclusion of contractors and the rejection of bids submitted under conditions of an act of unfair competition. However, under the provisions of Public Procurement Law, the definition of bid collusion derived from antitrust law has been modified, which has measurable consequences for the application of these provisions by contracting authorities and judicial authorities.
Ekonomia XXI Wieku = Economics of the 21st Century, 2023, Nr 26, s. 27-37